Clinical utility of extended monocytes parameters as a screening tool in suspected dengue infection - Nur Aliaa; Mohd Tohit, Eusni Rahayu; Nik Mustapha, Nik Hafidzah; Osman, Malina; Seman, Zainina (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Increased monocyte percentage and monocyte anisocytosis were suggested as new markers for dengue fever detection. This study aims to investigate and evaluate monocyte volume standard deviation (MoV-SD) and monocyte percentage (Mono %) parameters using Coulter automated haematology analyser as screening parameters in discriminating between dengue infection and other febrile illness. Methods: A cross-sectional laboratory analysis using suspected dengue fever patients were included in this study. The study was conducted in the Department of Pathology, Hospital Tuanku Jaafar Seremban from June 2016 until June 2017. Patients were classified into dengue positive and dengue negative based on dengue IgM and NS1 result. The diagnostic performance of MoV-SD and Mono % was analysed by receiver operating characteristic (ROC) curve analysis. The cut-off value of the MoV-SD and Mono % was determined and evaluated with the validation group. Chi-square test was used to assess the association between the parameters. Results: 88 (48.4%) from 182 samples were confirmed to have dengue infection. ROC curve analysis showed Mono % at cut off value of 10.5 % with area under the curve (AUC) of 0.869 with 84.1% sensitivity and 84% specificity (95% CI: 0.812-0.925) and MoV-SD cut off value at 22.2 (AUC 0.776, 80.7% sensitivity, 61.7% specificity, 95% CI: 0.709-0.843) are an excellent parameters in separating dengue positive and dengue-negative patients. A cut-off value of 10.5 of Mono % and 22.2 of MoV-SD were applied to the validation group showed 83.1%, 66.4% sensitivity and 84.9%, 77.3% specificity respectively. Conclusion: MoV-SD and Mono % parameters are a potential parameter for the screening of dengue infection in acute febrile illness patients with good specificity and sensitivity.